Neuropathology of AIDS: An Autopsy Review of 284 Cases from Brazil Comparing the Findings Pre- and Post-HAART (Highly Active Antiretroviral Therapy) and Pre- and Postmortem Correlation. (22nd February 2012) - Silva, Ana Cristina Araújo Lemos; Rodrigues, Blenda Sousa Carli; Micheletti, Adilha Misson Rua; Tostes, Sebastião; Meneses, Antonio Carlos Oliveira; Silva-Vergara, Mário Leon; Adad, Sheila Jorge
Abstract : A retrospective study of central nervous system (CNS) in 284 autopsy AIDS cases in Brazil (1989–2008) divided into 3 groups: A (without antiretroviral treatment: 163 cases); B (other antiretroviral therapies: 76 cases); C (HAART for 3 months or more: 45 cases). In 165 (58.1%) cases, relevant lesions were found, predominantly infections (54.2%); the most frequent was toxoplasmosis (29.9%) followed by cryptococcosis (15.8%), purulent bacterial infections (3.9%), and HIV encephalitis (2.8%); non-Hodgkin lymphomas occurred in 1.4% and vascular lesions in 1.1%. There was no difference when compared the frequency of lesion among the groups; however, toxoplasmosis was less common while HIV encephalitis was more frequent in group C related to A. CNS lesions remain a frequent cause of death in AIDS; however, the mean survival time was four times greater in group C than in A. In 91 (55.1%) of 165 cases with relevant brain lesions (or 32% of the total 284 cases), there was discordance between pre- and postmortem diagnosis; disagreement type 1 (important disease that if diagnosed in life could change the patient prognosis) occurred in 49 (53.8%) of 91 discordant cases (17.6% of the total 284) indicating the autopsy importance, even with HAART and advanced diagnostics technologies.